A policy analysis using analytical hierarchical Process (AHP): A case of Keretapi Tanah Melayu (KTM) - Mat Zin, Razali (Universiti Utara Malaysia, 1986)
The major concern of this analysis is to search for the most effective institutional administrative arrangement which will improve the management of the KTM.The model used in this analysis was Analytical Hierarchical Process (AHP) introduced by Saaty and Kevin.The policy options considered and analyzed are: 1.The Status Quo -FUN Government Ownership 2.Equal Between the Federal Govcmment and a Foreign Government 3.Join t-ven htre between Federal Government and a Foreign Government.4.Pn'vatization by Indigenous Private Investors With Government Regulations. 5.Contracting Out to Indigenous Private Concern With a Provision of Greater Autonomy. Finally, based on the above analysis, we make a recommendation on the best option, i.e., to manage the KTM by indigenous privateownership (option 4).